2020
DOI: 10.3390/ijerph17082946
|View full text |Cite
|
Sign up to set email alerts
|

Residential Radon Exposure and Cigarette Smoking in Association with Lung Cancer: A Matched Case-Control Study in Korea

Abstract: Residential radon exposure and cigarette smoking are the two most important risk factors for lung cancer. The combined effects thereof were evaluated in a multi-center matched case-control study in South Korea. A total of 1038 participants were included, comprising 519 non-small cell lung cancer cases and 519 age- and sex- matched community-based controls. Residential radon levels were measured for all participants. Multivariate logistic regression was used to calculate odds ratios (OR) for lung cancer accordi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Radon-attributable lung cancer deaths for all 66 countries totaled 226,057 in 2012 and represented a median of 3.0% of total cancer deaths [77]. Recently, multiple published studies have measured the risk of developing lung cancer following residential or occupational radon exposure in various regions of the world, as well as the synergistic effect of cigarette smoking and the effect in never-smokers [8][9][10]73,[77][78][79][80][81] as well as analyzing the histological types of lung cancer [82].…”
Section: Radon-attributable Lung Cancer Riskmentioning
confidence: 99%
“…Radon-attributable lung cancer deaths for all 66 countries totaled 226,057 in 2012 and represented a median of 3.0% of total cancer deaths [77]. Recently, multiple published studies have measured the risk of developing lung cancer following residential or occupational radon exposure in various regions of the world, as well as the synergistic effect of cigarette smoking and the effect in never-smokers [8][9][10]73,[77][78][79][80][81] as well as analyzing the histological types of lung cancer [82].…”
Section: Radon-attributable Lung Cancer Riskmentioning
confidence: 99%
“…The association between radon exposure and lung cancer has been widely reported, and the combined effect of radon and tobacco smoke is thought to be synergic and higher than additive, rising 20 to 25 times higher than the risk of death by lung cancer in smokers exposed to radon beyond 200 Bq/m 3 [11,[75][76][77].…”
Section: Radon Tobacco and Other Carcinogensmentioning
confidence: 99%
“…In 2001, Lagarde et al suggested the existence of a synergistic effect between indoor radon exposure and tobacco smoke with a relative excess risk of 0.29 (95% CI, 0.03-1.24). Moreover, a recent study has described that smokers exposed to radon below 37 Bq/m 3 had a risk of developing lung cancer of 20.16 (95%CI, 3.4-118.6) [39,76,78].…”
Section: Radon Tobacco and Other Carcinogensmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect was also shown in humans. In the matched case-control study conducted in Korea it was proved that exposure to residential radon and smoking had a synergistic effect increasing the risk of developing lung cancer [ 130 ].…”
Section: Radon and Lung Cancermentioning
confidence: 99%